A PHENOMENOLOGICAL STUDY ON EMPLOYEES’ SUBJECTIVE EXPERIENCES OF E-HRM PRACTICES IN THE ERA OF DIGITAL TRANSFORMATION - Dedy Putro Triyuwono; Ahmad Ihsanul Anhar; Sulastini; Syahrial Shaddiq (Jurnal Riset Multidisiplin Edukasi, 2025)
The rapid rise of Industry 4.0 has driven organizations globally to adopt Electronic Human Resource Management (e-HRM) systems as part of digital transformation. Yet, in developing countries, e-HRM implementation still faces socio-cultural and structural barriers, often overlooked from employees’ subjective perspectives. This study explores how employees construct meaning and interpret everyday experiences with e-HRM practices in Indonesia. Using an interpretative phenomenological approach, data were collected through semi-structured interviews, participatory observations, and document analysis in a tech startup and a medium-scale manufacturing company. Purposive and snowball sampling captured diverse viewpoints. Thematic analysis revealed three key themes: perceived benefits and barriers of e-HRM technology, changing patterns of workplace social interaction, and the reconstruction of work identity in digital HR contexts. Verbatim quotations illustrate employees’ negotiation between efficiency and social connectedness. Theoretically, this research applies Symbolic Interactionism and Social Phenomenology to deepen understanding of subjective meaning-making in HR digitalization. Practically, the findings highlight the importance of adaptive, human-centered e-HRM strategies that balance technological automation with meaningful social ties. These insights offer organizations guidance to develop inclusive digital HR policies responsive to the realities of Industry 4.0.